The ANALYSIS OF FINE MOTOR DEVELOPMENT IN GROUP B IN COUNTRY PAUD DEVELOPMENT 1 BENGKULU CITY - Beno, Rossa; Nurwita, Syisva; Margaretha, Lydia (Early Childhood Research and Practice, 2023)
The purpose of this study was to find out whether meronce activities can help develop fine motor skills in group B children at PEMBINA I PAUD Negeri Bengkulu City. Data collection techniques using the method of observation, interviews and documentation. Data analysis was carried out in a qualitative descriptive manner, with the emphasis being used to determine the process improvement expressed in a predicate.